Case reportInterventional treatment of haemodynamically interrupted aortic arch with stent implantation in a 9-year-old patient – a case report - Dryżek, Paweł; Góreczny, Sebastian; Politowska, Beata; Moszura, Tomasz; Kobielski, Artur; Sysa, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
A case of percutaneous treatment of haemodynamically interrupted aortic arch in a 9-year-old patient is reported. Congenital heart disease was diagnosed late in school age during routine physical examination, which revealed arterial hypertension. In further non-invasive diagnostic tests, echocardiography and computed tomography, critical coarctation of aorta was visualized. The patient underwent left heart catheterization with CP stent implantation. The stent fully expanded the stenosed aortic isthmus to 14 mm with no pressure gradient in direct haemodynamic measurement. No complications during or after the intervention were observed. In one-year follow-up the patient remains asymptomatic with no signs of restenosis.